Large-scale optimization of households with photovoltaic-battery system and demand response - Lezama, Fernando (2021)
The adoption of distributed resources by households, e.g., storage units and renewables, open the possibility of self-consumption (on-site generation), sell energy to the grid as a small producer, or do both according to the context of operation. In this paper, a framework capturing the interactions between an aggregator and a large number of households is envisaged. We consider households equipped with distributed resources and simple smart technologies that look for the reduction of energy bills and can perform demand response actions. A mixed-integer linear programming formulation that provides optimal scheduling of household devices and minimal operation costs is developed. Results show that the model can be applied considering up to 10000 households. Moreover, households can reduce up to 20% of their energy bill on average using storage units and demand response. Besides, the aggregator can attain profits by offering the resulting flexibility to upper-level players of the energy chain, such as the distribution system operator.